2022
DOI: 10.3389/fpubh.2022.929840
|View full text |Cite
|
Sign up to set email alerts
|

Heart diseases, hypertension and effects of antihypertensive medications: Is hypertension a true risk factor of heart diseases?

Abstract: BackgroundHeart diseases (HD) are the leading cause of deaths in the world. Many studies have been done on the relationships among hypertension, HD and antihypertensive medications. Most of the studies find that hypertension is a significant risk factor of HD, but there are some studies in which hypertension is not a risk factor. As antihypertensive medications are routinely prescribed to prevent HD, it is necessary to evaluate the effects of these and other risk factors of HD.Data and methodsThe relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The results of Table 4 suggest that the (standardized) difference between SBP and DBP does matter, but the BP level may be less important. There have been many studies on the relationship between BP and diseases (especially cardiovascular diseases) ( 50 ). Therefore, it might be necessary to reevaluate the relationship between BP and disease from this viewpoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Table 4 suggest that the (standardized) difference between SBP and DBP does matter, but the BP level may be less important. There have been many studies on the relationship between BP and diseases (especially cardiovascular diseases) ( 50 ). Therefore, it might be necessary to reevaluate the relationship between BP and disease from this viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Nawata ( 50 ), the selection of covariates is important. If we do not add the appropriate covariates, we obtain misleading results.…”
Section: Data and Modelsmentioning
confidence: 99%
“…There are several classes of antihypertensive medications, including diuretics, beta-blockers, ACE inhibitors, angiotensin receptor blockers (ARBs), calcium channel blockers, and renin inhibitors. These medications work by different mechanisms, but all aim to reduce blood pressure by relaxing blood vessels, decreasing blood volume, or reducing the activity of the renin-angiotensin-aldosterone system [55]. Antihypertensive medications are typically prescribed for individuals with high blood pressure, which is defined as a blood pressure reading of 130/80 mmHg or higher.…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%
“…The selection of appropriate covariates is very important. Nawata [55] showed that SBP was strongly associated with the occurrence of heart disease when the two variables were directly compared. However, the importance of SBP diminished when other covariates were included, suggesting that this relationship may be spurious.…”
Section: Selection Of Covariatesmentioning
confidence: 99%